Histological and immunological reaction of cattle skin to first-instar larvae of Dermatobia hominis - OliveiraSequeira, TCG; Sequeira, Julio Lopes [UNESP]; Schmitt, F. L.; DeLello, E. (Blackwell Science, 1996)
Six cattle that had earlier exposure to Dermatobia hominis were infested experimentally with first-instar larvae of the parasite. Skin biopsies taken at intervals were studied in wax and in plastic sections. The avidin-biotin-peroxidase method was used to detect the presence and localization of host immunoglobulins (Igs) G and M and antigens of first and second instar larvae of Dermatobia hominis. The larvae penetrated actively through the skin and migrated towards the subcutaneous tissues. The great numbers of eosinophils suggest that they are the most important cell in mediating damage to D.hominis larvae. The immunoglobulins bound only to dead or moulting larvae in which access to binding sites may have been altered. This could represent a morphological manifestation of a mechanism that protects larvae from the host immune response. Large amounts of soluble antigens detected along the fistulous tract may be important in the maintenance of this tract by disturbing the normal cicatrization process.
Keywords: Dermatobia hominis; cattle; eosinophils; basophils; mast cells; immuno-histochemistry; antigens; immunoglobulins